Pengaruh Persepsi Harga dan Kualitas Jaringan terhadap Keputusan Pembelian (Studi Kasus pada Mahasiswa UNY Kampus Wates yang Menggunakan Kartu Internet Indosat) - wizdan choiriyah (ASSET: Jurnal Manajemen dan Bisnis, 2018)
This research aims to know: (1) influence of price perception of Indosat Internet card purchase decision, (2) Effect of network quality on the purchase decision of Indosat's Internet card, (3) influence the perception of price and network quality simultaneously to the decision of the purchase of Indosat Internet card at UNY campus Wates. This research is a quantitative study with the survey method using questionnaires. The population used in this study is the entire UNY student Wates campus. Samples were taken as many as 95 respondents using the Purposive sampling method. The instrument validity test uses Confirmatory Factor Analysis, while the reliability test uses Cronbach Alpha. The analytical techniques used are prerequisite test analysis, multiple linear regression analysis, hypothesis testing and coefficient of determination.The results of this study show that: (1) Perception of Price has a positive and significant effect on purchasing decisions with a T-calculate value of 2.537, significance value of 0.013, and regression coefficient has a positive value of 0.245, (2) The network quality has a positive and significant effect on purchasing decisions with a T-count value of 2.870, the significance value of 0.005 , (3) The perception of simultaneous price and network quality has a positive and significant effect on purchasing decisions with a statistical result of F-Calculate of 9.369, the significance of 0.000, (4) The influence of perception of price and network quality of the purchase decision (adjusted R2) is 0.169 (16.9%).